Handbook of industrial mixing : science and practice - Paul, Edward L.; Atiemo-Obeng, Victor A.; Kresta, Suzanne M. (Wiley-Interscience, 2004)
Annotation Handbook of Industrial Mixing will explain the difference and uses of a variety of mixers including gear mixers, top entry mixers, side entry mixers, bottom entry mixers, on-line mixers, and submerged mixers The Handbook discusses the trade-offs among various mixers, concentrating on which might be considered for a particular process. Handbook of Industrial Mixing explains industrial mixers in a clear concise manner, and also:* Contains a CD-ROM with video clips showing different type of mixers in action and a overview of their uses.* Gives practical insights by the top professional in the field.* Details applications in key industries.* Provides the professional with information he did receive in school.
"Sponsored by the North American Mixing Forum."
Keywords: Mixing -- Handbooks, manuals, etc.; elektronické knihy; electronic books